FTREATMENT ADHERENCE IN HYPERTENSIVE PATIENTS AND ASSOCIATED FACTORS AT NGA NAM TOWN MEDICAL CENTER, SOC TRANG PROVINCE IN 2024 (Vietnam Journal of Community Medicine, 2026)
Objective: To determine the prevalence of treatment adherence and associated factors among outpatients with hypertension at Nga Nam Medical Center, Soc Trang Province, in 2024.Subjects and Methods: A descriptive cross-sectional study was conducted on 350 outpatients with hypertension. Medication adherence was assessed using the 8-item Morisky Medication Adherence Scale (MMAS-8); patients were considered adherent when they achieved an MMAS-8 score of ≥6. Overall treatment adherence was defined as meeting at least 4 out of 5 treatment criteria, including medication adherence and lifestyle modifications.Results: The overall treatment adherence rate was 56.6%. Medication adherence was 47.42%, while adherence to diet; non-smoking, restricted alcohol consumption; blood pressure monitoring, and physical activity were 83.14%, 59.14%, 83.71%, and 12.0%, respectively. Following multivariate analysis, factors associated with treatment adherence included female gender (aOR=1.62) and absence of comorbidity (OR=1.84); while advanced age (aOR=0.74) and prolonged duration of hypertension (aOR=0.63) reduced the adherence rate.Conclusion: Overall treatment adherence was moderate, and adherence to medication and physical activity remained low. Males, advanced age, and long disease duration are groups that require prioritized intervention to improve treatment adherence.
Keywords: hypertension, treatment adherence, lifestyle modification, associated factors, outpatient.